1971
DOI: 10.1111/j.1365-2621.1971.tb15143.x
|View full text |Cite
|
Sign up to set email alerts
|

Dieldrin Residues in Sausage Patties Cooked by Three Methods

Abstract: SUMMARY The effect of cooking by pan frying, baking and microwave energy on dieldrin residue levels in pork sausage was determined. Sausage was prepared from right shoulders taken from three animals, two having received known quantities of the pesticide and one no oral doses of the pesticide. Acetonitrile partitioning followed by Florisil‐Celite column clean‐up and electron capture gas chromatography was used to determine dieldrin residue levels. No significant differencs attributable to cooking method were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1971
1971
1992
1992

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Liver slices and pork loin chops were braised to internal temperatures of 80 and 75 °C, respectively, as described by Maul et al (1971). The equipment and procedures outlined by Funk et al (1971) were used to pan-fry liver slices to 80 °C as well as to pan-fry sausage patties, pork loin chops, and ham to 75 °C. Tongue was pressure cooked for 40 min at 15 psi following the procedures of Smith et al (1977).…”
Section: Methodsmentioning
confidence: 99%
“…Liver slices and pork loin chops were braised to internal temperatures of 80 and 75 °C, respectively, as described by Maul et al (1971). The equipment and procedures outlined by Funk et al (1971) were used to pan-fry liver slices to 80 °C as well as to pan-fry sausage patties, pork loin chops, and ham to 75 °C. Tongue was pressure cooked for 40 min at 15 psi following the procedures of Smith et al (1977).…”
Section: Methodsmentioning
confidence: 99%
“…Fat rendering has been suggested as the major mode for pesticide removal (Ritchey et al, 1969(Ritchey et al, , 1972Morgan et al, 1972). Although fat rendering has been found by all investigators to reduce pesticide levels, other data suggest that additional mechanisms also may be important (Yadrick et al, 1971;Funk et al, 1971). Funk et al (1971) reported dieldrin losses during the baking of sausage patties to be 42 and 46%.…”
Section: Dieldrinlevelsmentioning
confidence: 99%
“…Although fat rendering has been found by all investigators to reduce pesticide levels, other data suggest that additional mechanisms also may be important (Yadrick et al, 1971;Funk et al, 1971). Funk et al (1971) reported dieldrin losses during the baking of sausage patties to be 42 and 46%. However, the drip accounted for only 9 and 4% of these losses, respectively.…”
Section: Dieldrinlevelsmentioning
confidence: 99%